Land uplift linked to managed aquifer recharge in the Perth Basin, Australia - Parker, Amy; Pigois, J.P.; Filmer, Mick; Featherstone, Will; Timms, Nick; Penna, N.T. (2021)
While the link between groundwater extraction and land subsidence is well documented, observations of land uplift associated with groundwater replenishment are less so. In the Perth Basin, Western Australia, a programme of managed aquifer recharge (MAR) commenced in August 2017 and is designed to sustain levels of hydraulic head in aquifers valuable for extraction. Space-based TerraSAR-X satellite radar measurements were used to capture the first 3.5 years of MAR, providing an insight into the evolution of ground uplift in the Perth Basin that is spatially and temporally related to the MAR injection volumes and the injection-induced changes in hydraulic head. Significantly, the X-band InSAR has spatial coverage around the single injection point, and the time series begins prior to the start of the injection, rather than a generalised study of ground surface and aquifer change from multiple groundwater recharge contributions. This enables the observed ground uplift to be correlated with the time of initial injection, pause, then resumption with increased volumes. The X-band InSAR identified maximum displacements of up to 20±3 mm in the vicinity of the injection bores, but which subside when injection is paused. The spread of displacements from the injection site extends over 14 km southwards with the dispersion pattern identifying linear boundaries that sharply delineate displacements in the north-west and north-east. The extent of the region impacted by ground uplift is likely linked to the distribution of extraction bores and heterogeneities in the subsurface geology, including a persistent linear feature that has not yet been considered in hydrogeological models of the region. This article focusses on the immediate surface response to the MAR injection, and identifying the constraining physical features for the injected recharge, thus providing an additional insight into the challenging and complex Perth Basin. It also demonstrates the millimetric accuracy possible from X-band radar satellites that permits MAR volumes to be managed to avoid infrastructure damage that may undermine public confidence in the MAR program.